Characterization of a Novel Male Pheromone Compound in Leucoptera sinuella (Lepidoptera: Lyonetiidae) and Its Role in Courtship Behavior - Laura Sánchez-Aros; Abel F. O. Queiroz; Jorge Guajardo; Wilson Barros-Parada; Glenn P. Svensson; Jan Bergmann (Insects)
The poplar moth, Leucoptera sinuella (Lepidoptera: Lyonetiidae), is widely distributed across Europe, Asia, and parts of Africa. It was first identified in Chile in 2015 and has since become a significant pest in the agricultural sector. Additionally, economic losses are further aggravated by the presence of L. sinuella pupae in nearby fruit orchards. This study investigated the presence of a male-produced sex pheromone in L. sinuella, focusing on the hairpencil (HP) glands, which are known as dissemination structures for male pheromones in lepidopterans. Male HP glands were solvent-extracted and analyzed by gas chromatography–mass spectrometry. Chemical microderivatization and comparisons of mass spectra and retention indices of natural compounds with synthetic standards led to the identification of two compounds: (Z)-3-decenyl hexanoate (the major component) and (Z)-3-decen-1-ol (a minor component). Although electrophysiological assays did not show detectable antennal responses to (Z)-3-decenyl hexanoate, behavioral bioassays demonstrated its role as a short-range courtship signal in L. sinuella. Males with ablated hairpencils exhibited significantly reduced courtship success compared to controls; however, exposure of females to synthetic (Z)-3-decenyl hexanoate or HP extract restored male courtship success. To our knowledge, (Z)-3-decenyl hexanoate has not been previously reported as a sex pheromone component in any insect species, making this discovery an intriguing addition to the diversity of chemical communication in insects.